Factors affecting behaviour of Income Zakat payment among FELDA settlers during COVID-19 Pandemic - Hairunnizam Wahid; Anida Norlena Salim; Mohamad Syahmi Mat Daud; Mohd Adib Ismail (Center of Strategic Studies (PUSKAS) BAZNAS, 2022)
As a Muslim who believes in Allah SWT, the responsibility to give zakat is one of the beliefs that must be implemented. And a Muslim should spend part of the property sincerely because Allah pleases alms. Internal and external factors that occur around an individual will affect his thoughts and behavior. Since the declaration of the COVID-19 pandemic announced by the World Health Organization (WHO), the whole world has been at war with the pandemic phenomenon of coronavirus outbreak. During that period, the world seemed to experience a